2021
DOI: 10.31925/farmacia.2021.6.7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Capacity of Human Serum Albumin to Reduce Non-Specific Binding of Meloxicam in the Ultrafiltration Process

Abstract: Due to the importance that plasma protein binding of drugs plays and the constant interest to optimize study methods of the process, this study aimed to test the capacity of a human serum albumin solution to reduce non-specific binding of highly bound meloxicam, based on the ability of the protein to block most non-specific binding sites of the ultrafiltration devices. Samples of meloxicam and internal standard piroxicam were prepared in both phosphate-buffered saline solution, commonly used in biological rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Regarding the main known disadvantage of the method represented by the nonspecific binding (NSB) of drugs to parts of the UF device, we considered it to be negligible in our study, taking into consideration the literature reports made by Wang and Williams, who have shown that even in the case of highly lipophilic compounds, NSB is not a limitation when drugs are incubated with the UF device in protein matrices because of their ability to block the NSB sites 37 . This theory was also tested and proven in our previous experience 38 …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Regarding the main known disadvantage of the method represented by the nonspecific binding (NSB) of drugs to parts of the UF device, we considered it to be negligible in our study, taking into consideration the literature reports made by Wang and Williams, who have shown that even in the case of highly lipophilic compounds, NSB is not a limitation when drugs are incubated with the UF device in protein matrices because of their ability to block the NSB sites 37 . This theory was also tested and proven in our previous experience 38 …”
Section: Resultsmentioning
confidence: 96%
“…37 This theory was also tested and proven in our previous experience. 38 The concentrations of carvedilol for the binding assays ranges were chosen taking into account the maximum plasma concentrations detected in patients reported in previous studies. Depending on the dose regimen and type of pharmaceutical formulation administered (immediate release, controlled release), a great variability regarding the maximum plasma concentration was often observed with ranges that could go from a value below 7 ng/mL to a value over 350 ng/mL.…”
Section: Determination Of the Degree Of Binding Of Cvd And Its Enanti...mentioning
confidence: 99%
“…According to the data sheet of the product, only the Centrifree devices were specifically designed for separating free from bound microsolutes in biological samples, but other PPB studies report good results also obtained using the Amicon Ultra devices, initially designed for concentration of different components of biological samples (antigens, antibodies, enzymes, nucleic acids, microorganisms), protein extraction and purification (Du et al, 2014;Imre et al, 2021).…”
Section: Classical Ultrafiltration Methodsmentioning
confidence: 99%